Pemafibrate Prevents Rupture of Angiotensin II-Induced Abdominal Aortic Aneurysms - Amioka, Naofumi; Miyoshi, Toru; Yonezawa, Tomoko; Kondo, Megumi; Akagi, Satoshi; Yoshida, Masashi; Saito, Yukihiro; Nakamura, Kazufumi; Ito, Hiroshi (Frontiers in Cardiovascular Medicine, 2022)
Background: Abdominal aortic aneurysm (AAA) is a life-threatening disease that lacks effective preventive therapies. This study aimed to evaluate the effect of pemafibrate, a selective peroxisome proliferator-activated receptor alpha (PPARα) agonist, on AAA formation and rupture. Methods: Experimental AAA was induced by subcutaneous angiotensin II (AngII) infusion in ApoE-/- mice for 4 weeks. Pemafibrate (0.1 mg/kg/day) was administered orally. Dihydroethidium staining was used to evaluate the reactive oxygen species (ROS). Results: The size of the AngII-induced AAA did not differ between pemafibrate- and vehicle-treated groups. However, a decreased mortality rate due to AAA rupture was observed in pemafibrate-treated mice. Pemafibrate ameliorated AngII-induced ROS and reduced the mRNA expression of interleukin-6 and tumor necrosis factor-α in the aortic wall. Gelatin zymography analysis demonstrated significant inhibition of matrix metalloproteinase-2 activity by pemafibrate. AngII-induced ROS production in human vascular smooth muscle cells was inhibited by pre-treatment with pemafibrate and was accompanied by an increase in catalase activity. Small interfering RNA-mediated knockdown of catalase or PPARα significantly attenuated the anti-oxidative effect of pemafibrate. Conclusions: Pemafibrate prevented AAA rupture in a murine model, concomitant with reduced ROS, inflammation, and extracellular matrix degradation in the aortic wall. The protective effect against AAA rupture was partly mediated by the anti-oxidative effect of catalase induced by pemafibrate in the smooth muscle cells.